(untitled) (International journal of artificial intelligence, 2026)
The Khorezm region of Uzbekistan, characterized by a sharply continental desert climate with hot, dry summers, cold winters, low precipitation (approximately 78–80 mm annually), and significant temperature fluctuations, plays a critical role in melon (Cucumis melo L.) cultivation. This article examines how these climatic factors influence the incidence and development of major melon diseases such as Fusarium wilt, powdery mildew, Alternaria, and root rot. High summer temperatures (often exceeding 30–35°C) combined with low humidity favor certain fungal pathogens, while irrigation practices and soil salinity exacerbate root diseases. Based on field observations, literature analysis, and regional data, the study highlights correlations between climatic parameters (temperature, humidity, drought stress) and disease severity. Recommendations include the use of resistant varieties, optimized irrigation, and integrated pest management to mitigate climate-driven risks. This research underscores the need for adaptive strategies in the face of ongoing climate change in arid zones.